2014
DOI: 10.4028/www.scientific.net/amr.979.248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing Treatment on WO<sub>3</sub> Thin Films Prepared by DC Reactive Magnetron Sputtering

Abstract: Tungsten trioxide (WO3) thin films were prepared by a DC reactive magnetron sputtering technique. The thin film fabrication process used tungsten (99.995%) as the sputtering target, the mixture of argon and oxygen as sputtering and reactive gases, and silicon (100) and glass slides as the substrates. The effects of annealing temperature in the range of 200-400°C on physical and optical properties of the WO3 thin films were investigated. The nanostructures and morphologies of these films were characterized by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…The XRD data ( Figure 5 ) of a 60 nm-thick NS-WO x film reveals an amorphous nature of the as-deposited film, which transforms into a polycrystalline monoclinic structure after vacuum annealing. A similar observation is reported in literature where the as-deposited amorphous WO x films transformed into monoclinic structures after annealing at or above 673 K [ 2 , 12 , 46 ]. It is to be noted that no apparent peak is visible in annealed films having thicknesses less than or equal to 30 nm ( Figure 5 , inset).…”
Section: Resultssupporting
confidence: 88%
“…The XRD data ( Figure 5 ) of a 60 nm-thick NS-WO x film reveals an amorphous nature of the as-deposited film, which transforms into a polycrystalline monoclinic structure after vacuum annealing. A similar observation is reported in literature where the as-deposited amorphous WO x films transformed into monoclinic structures after annealing at or above 673 K [ 2 , 12 , 46 ]. It is to be noted that no apparent peak is visible in annealed films having thicknesses less than or equal to 30 nm ( Figure 5 , inset).…”
Section: Resultssupporting
confidence: 88%
“…Numerous studies reported different synthesis approaches of WO 3 nanostructures, including sol-gel technique [22][23][24], electrochemical deposition [25], chemical vapor deposition [26,27], electrochemical oxidation [28,29], magnetron sputtering [30][31][32], ion-beam evaporation [33,34], and atomic layer deposition [35], which have been described. Among them, an anodization technique attracts considerable attention due to its low cost and the simplicity of a synthesis route.…”
Section: Introductionmentioning
confidence: 99%